An Internal Control Analysis of Credit Sales at Imported Meat Distributors in Cirebon Regency: Operational and Educational Perspectives - Aizzudin, Muhamad; Indriyani, Rinni; Sari, Fitriya (Journal Corner of Education, Linguistics, and Literature, 2025)
This study analyzed the effectiveness of internal control over credit sales at an imported meat distributor in Cirebon, Indonesia, using the COSO framework. Data were collected through observations, interviews, and document analysis. The results reveal that the current control system does not fully align with COSO’s five components—control environment, risk assessment, control activities, information and communication, and monitoring. From an educational standpoint, this case serves as a valuable resource for students, educators, and practitioners in accounting and business management. It provides a practical example of how theoretical internal control concepts apply to small and medium-sized enterprises (SMEs), highlighting the need for structured risk assessment, segregation of duties, and integrated accounting systems. The study offers recommendations for operational improvement while also suggesting curriculum enhancements for professional training programs.